Historical Evolution of Spatial Abilities - A. Ardila (Behavioural Neurology)
Historical evolution and cross-cultural differences in spatial abilities are analyzed. Spatial abilities have been found to be significantly associated with the complexity of geographical conditions and survival demands. Although impaired spatial cognition is found in cases of, exclusively or predominantly, right hemisphere pathology, it is proposed that this asymmetry may depend on the degree of training in spatial abilities. It is further proposed that spatial cognition might have evolved in a parallel way with cultural evolution and environmental demands. Contemporary city humans might be using spatial abilities in some new, conceptual tasks that did not exist in prehistoric times: mathematics, reading, writing, mechanics, music, etc. Cross-cultural analysis of spatial abilities in different human groups, normalization of neuropsychological testing instruments, and clinical observations of spatial ability disturbances in people with different cultural backgrounds and various spatial requirements, are required to construct a neuropsychological theory of brain organization of spatial cognition.